2012
DOI: 10.1177/0956797612440101
|View full text |Cite|
|
Sign up to set email alerts
|

Early Predictors of High School Mathematics Achievement

Abstract: Identifying the types of mathematics content knowledge that are most predictive of students' long-term learning is essential for improving both theories of mathematical development and mathematics education. To identify these types of knowledge, we examined long-term predictors of high school students' knowledge of algebra and overall mathematics achievement. Analyses of large, nationally representative, longitudinal data sets from the United States and the United Kingdom revealed that elementary school studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
502
0
25

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 630 publications
(553 citation statements)
references
References 13 publications
26
502
0
25
Order By: Relevance
“…Hypothesis 2). These results are in line with the major findings of previous studies with U.S. samples (see Bailey et al, 2012;Booth & Newton, 2012;Siegler et al, 2012;Siegler & Pyke, 2013;Siegler et al, 2011) and thus indicate that prior findings on this topic are not limited to the U.S.…”
Section: Fraction Magnitude Understanding As a Key For General Math Dsupporting
confidence: 82%
See 4 more Smart Citations
“…Hypothesis 2). These results are in line with the major findings of previous studies with U.S. samples (see Bailey et al, 2012;Booth & Newton, 2012;Siegler et al, 2012;Siegler & Pyke, 2013;Siegler et al, 2011) and thus indicate that prior findings on this topic are not limited to the U.S.…”
Section: Fraction Magnitude Understanding As a Key For General Math Dsupporting
confidence: 82%
“…Also as with whole numbers, fraction magnitude understanding has proved to be quite strongly correlated with other aspects of mathematics learning. On top of this correlational evidence, recent investigations provide evidence for predictive relations between earlier fraction magnitude understanding and subsequent knowledge of fraction arithmetic, algebra and overall math achievement (Bailey et al, 2012;Booth & Newton, 2012;Siegler et al, 2012). To cite one example, Siegler et al (2012) demonstrated that 5 th graders' fraction knowledge predicts their mastery of algebra and overall mathematics achievement in high school, 5 or 6 years later, even after controlling for IQ, reading achievement, working memory, family income and education, and whole number knowledge.…”
Section: Previous Studies On Fraction Understandingmentioning
confidence: 99%
See 3 more Smart Citations